Penerapan Metode Pembelajaran Muhadatsah Yaumiyah dalam Meningkatkan Maharatul Kalam pada Siswa Kelas X Qur’anic School of Al-Muthi’ah Mojolaban Sukoharjo Tahun Ajaran 2024/2025 - Roudotul Hasna (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2024)
This study aims to improve Arabic speaking skills (maharat al-kalam) through the implementation of the muhadatsah yaumiyah method among 10th-grade female students at SMA Qur’anic School of Al-Muthi’ah, Sukoharjo. The research was motivated by students' low verbal communication ability and the ineffectiveness of the previously applied teaching methods. This Classroom Action Research (CAR) was conducted in two cycles using a qualitative descriptive approach and involved seven students. Data were collected through observation, interviews, and documentation. The results showed that the muhadatsah yaumiyah method enhanced students' confidence, speaking courage, and active participation in class. All students met the learning mastery criteria, indicating that the method is effective and suitable to be applied as a communicative and interactive strategy for teaching Arabic.